Costimulatory protein 4IgB7H3 drives the malignant phenotype of glioblastoma by mediating immune escape and invasiveness - Lemke, Dieter; Pfenning, Philipp-Niclas; Sahm, Felix; Klein, Ann-Catherine; Kempf, Tore; Warnken, Uwe; Schnölzer, Martina; Tudoran, Ruxandra; Platten, Michael; Wick, Wolfgang (Clinical cancer research, 2012)
Purpose: Recent work points out a role of B7H3, a member of the B7-family of costimulatory proteins, in conveying immunosuppression and enforced invasiveness in a variety of tumor entities. Glioblastoma is armed with effective immunosuppressive properties resulting in an impaired recognition and ineffective attack of tumor cells by the immune system. In addition, extensive and diffuse invasion of tumor cells into the surrounding brain tissue limits the efficacy of local therapies. Here, 4IgB7H3 is assessed as diagnostic and therapeutic target for glioblastoma. Experimental Design: To characterize B7H3 in glioblastoma, we conduct analyses not only in glioma cell lines and glioma-initiating cells but also in human glioma tissue specimens. Results: B7H3 expression by tumor and endothelial cells correlates with the grade of malignancy in gliomas and with poor survival. Both soluble 4IgB7H3 in the supernatant of glioma cells and cell-bound 4IgB7H3 are functional and suppress natural killer cell-mediated tumor cell lysis. Gene silencing showed that membrane and soluble 4IgB7H3 convey a proinvasive phenotype in glioma cells and glioma-initiating cells in vitro. These proinvasive and immunosuppressive properties were confirmed in vivo by xenografted 4IgB7H3 gene silenced glioma-initiating cells, which invaded significantly less into the surrounding brain tissue in an orthotopic model and by subcutaneously injected LN-229 cells, which were more susceptible to natural killer cell-mediated cytotoxicity than unsilenced control cells. Conclusions: Because of its immunosuppressive and proinvasive function, 4IgB7H3 may serve as a therapeutic target in the treatment of glioblastoma.